Analisa Perbandingan Kinerja Kontrol PID dan Fuzzy Logic Pada Sistem Load Frequency Control di Steam Power Plant - Yuliyanto Agung Prabowo; Pingky Tri Nur Rizky; Wahyu Setyo Pambudi; Lugas Jabbar Waskito (Universitas PGRI Kanjuruhan Malang, 2026)
Load Frequency Control (LFC) plays an essential role in maintaining frequency and power stability in power generation systems under load disturbances. Variations in load demand, such as increases or decreases, may lead to power deviations that affect system reliability; therefore, an effective control strategy is required. This study evaluates the performance of an LFC system by comparing a Proportional–Integral–Derivative (PID) controller and a Fuzzy Logic Controller (FLC). The system is modeled based on the dynamic characteristics of the governor, turbine, and generator of a coal-fired steam power plant. System performance is analyzed under three operating conditions: no disturbance, load increase, and load decrease. The evaluation focuses on maximum power deviation and settling time as performance indicators. Simulation results show that both controllers are able to maintain system stability but with different dynamic characteristics. Under no-disturbance conditions, the PID controller reaches stability faster with a settling time of 18.126 s, while the FLC requires 28.038 s. During load increases, the PID-controlled system stabilizes at 194.652 s, whereas the FLC reaches stability at 200.524 s. For load reductions, the PID controller stabilizes at 194.378 s and the FLC at 196.559 s. In terms of maximum power deviation, the FLC produces a smaller deviation (0.41%) compared to the PID controller (0.47%). These results indicate that the PID controller provides faster recovery, while the FLC offers smoother responses with smaller deviations, showing potential for improving LFC performance.